Hubungan daya tahan otot lengan dan percaya diri dengan kemampuan renang 50 meter gaya dada - Tjung Hauw Sin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2019)
The purpose of this study was to determine the relationship between endurance of the arm muscles and confidence in the ability to swim 50 meters breaststroke. The population numbered 39 athele and 32 samples were taken using the purposive sampling technique. This type of research uses descriptive correlational. The instruments used were pull-up tests, confidence questionnaires and the ability to swim 50 meters breaststroke. Data analysis uses simple correlation and multiple correlation. The results of the study were significant> 0.05, indicating that: (1) There was a correlation between endurance of the arm muscles and swimming ability of 50 meters breaststroke. (2) There is a relationship of confidence with the ability to swim 50 meters breaststroke. (3) There is a relationship between endurance of the arm muscles and confidence with the ability to swim 50 meters breaststroke.